MAKING A VACUUM CLEANER USING THE STEM EDUCATION SYSTEM IN STUDENTS' LABORATORY CLASSES (Web of Discoveries: Journal of Analysis and Inventions, 2023)
STEM this — S – science, T – technology, E – engineering and M – mathematics. When we translate from English into English, this is how it happens: natural sciences, technology, engineering, art and mathematics. We need to realize that these trends are becoming the most popular in the modern world. On this basis, today the STEM education system is developing as one of the main trends.